Blessing or curse? Government funding of deposit insurance and corporate lending - Delis, Manthos D.; Iosifidi, Maria; Papadopoulos, Panagiotis (Journal of Financial Stability, 2022)
A key policy to limit the possibility of bank runs is an explicit deposit insurance scheme, which can be either privately or government funded. Using syndicated loans from 63 countries during the period 1985–2016, we study the effect of government involvement in deposit insurance funding on price and non-price characteristics of loans. We show that changes from purely private-funded to either government-funded or jointly funded deposit insurance increase all-in-spread-drawn by approximately 4.6 %, further increase loan fees, decrease loan maturity, and increase the use of performance pricing provisions. Our findings are consistent with the moral hazard problem behind government-funded deposit insurance schemes.